The Effect of Fermentated Moringa Oleifera Leaf Water Extraction in Drinking Water on Physical Quality of Egg In Lohmann Brown Layer Hen Aged 80 Weeks - Y. K. P., Tarigan; Bidura, I G. N. G.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the effect of fermented Moringa oleifera leaves extract on Lohmann Brown chicken drinking water on the physical quality of eggs. The experimental design used was a completely randomized design (CRD) with three treatments and six replications, each replication using three Lohmann Brown chickens aged 80 weeks. The three treatments were Lohmann Brown chicken which was given drinking water without the addition of fermented Moringa oleifera leaf water extract as control (K0), Lohmann Brown chicken which was given 2% addition extract of fermented Moringa oleifera leaf water through drinking water (K1), and Lohmann Brown chicken given 4% addition of extract of water from Moringa oleifera leaves fermented through drinking water (K2). The variables observed in this study included egg weight average, egg white percentage, egg yolk percentage, eggshell percentage, and egg shell thickness. The results showed that the average egg weight, percentage of egg yolk, percentage of eggshell, eggshell thickness given fermented kelor leaf water extract was significant (P <0.05) higher than the control treatment, whereas in the percentage of egg white was real (P < 0.05) lower than the control treatment. Based on the results of the study, it can be concluded that the administration of fermented Moringa oleifera leaf extract in Lohman Brown chicken with a level of 2% and 4% can increase the average egg weight, yellow percentage, eggshell percentage, and egg shell thickness. While giving fermented ( Moringa oleifera ) leaf water extract with a level of 2% and 4% can reduce the percentage of egg white. Keywords: Lohmann Brown chicken, extract Moringa oleifera, egg quality.